Comparison of XP-endo Finisher, self-adjusting file, and Canal Brush systems on the removal of calcium hydroxide paste from root canals - Merve Yeniçeri Özata; Sadullah Kaya; Nihal Firdevs Özfidan Arıkan; Ezgi İlkay Zengin; Gizem Akın Tartuk (Mashhad University of Medical Sciences, 2023)
Introduction: This study aimed to compare the effectiveness of XP-endo Finisher (XPF), self-adjusting files (SAF), and Canal Brush (CB) systems in removing calcium hydroxide (CH) from an artificial standardized groove (ASG) created in the apical root area. Methods: Fifty-five mandibular premolar teeth were prepared to size Reciproc R40 and were split longitudinally. An ASG was prepared in the apical third of the root and filled with CH. The root halves were reassembled, and the samples were divided into two control groups [positive control and negative control (n=5)] and three experimental groups [XPF, SAF, and CB, (n=15)]. The results were evaluated according to a four-grade scoring system to assess the remained CH in ASGs. The statistical difference between the groups was analyzed using the Kruskal-Wallis test. Results: There was no statistically significant difference between the experimental groups in the ability to remove CH from the apical root thirds (P>0.05). Conclusion: None of the finishing techniques could completely clean CH. The SAF, XPF, and CB systems showed comparable efficacy in removing CH from the roots.  (J Dent Mater Tech 2023;12(1): 28-34)